A new implicit gradient damage model based on energy limiter for brittle fracture: Theory and numerical investigation - Tran, Hung Thanh; Bui, Tinh Quoc; Chijiwa, Nobuhiro; Hirose, Sohichi (Computer methods in applied mechanics and engineering, 2023)
We present a general form of the gradient-enhanced damage theory and its numerical implementation using finite element method (FEM) in modeling quasi-static brittle crack growth in one- (1D), two- (2D) and three-dimensional (3D) bodies. Coupled equations of the equilibrium and a new implicit gradient damage formulation are introduced to govern the deformation of the solid and evolution of the damage. The resulting nonlocal damage evolution equation featuring the growth of diffusive crack is integrated with a characteristic length scale to eliminate the common mesh-bias issue in FEM implementation. In contrast to the traditional gradient-enhanced damage approaches, the nonlocal damage field here is defined as the primary variable of the damage evolution equation without interpolation mismatch between the displacement and nonlocal damage fields. For derivation of the material constitutive law and local damage parameter, a novel strain energy density (SED) function based on the energy limiter theory for brittle crack growth problems under small strain regime is introduced. To further improve the performance of the developed model, an initial SED threshold, which is used for determining the critical point when damage starts to initiate in the material, is integrated into the novel energy limiter theory. For preventing nonphysical failure in compression domains, the spectral decomposition technique for the strain tensor is adopted to split the reference SED. With integrating the energy limiter into the developed theory, unlike the conventional nonlocal damage theories where the interpretation of the length scale is still ambiguous, the developed nonlocal damage model defines the length scale parameter as the problem-dependent factor. The performance and ability of the proposed model are demonstrated via a set of representative numerical examples in 1D, 2D and 3D fracture problems. •We present a new nonlocal damage model with energy limiter for brittle fracture.•Different from traditional approaches, the nonlocal damage variable is considered as a primary unknown.•A physic-based characteristic length scale is derived.•Material constitutive and local damage laws are redefined in terms of energy limiter and initial damage threshold.•The new damage models are insensitive to the meshes (mesh-independent solutions are obtained).